Penggunaan Biji Kacang Tanah sebagai Alternatif Kancing Genetika dalam Persilangan Monohibrid - Vidya Zachrani; Sari Oktavianti; Ida Yayu Nurul Hizqiyah; Windy Alifia Hikmatusolihat; Nandang Permadi (Program Studi Pendidikan Biologi, FKIP Unpas,, 2022)
Genetics is the basis for the development of biology and other sciences related to biology. The decline in traits or heredity has received the attention of many researchers. Monohybrid crosses are simple crosses that only pay attention to one trait or sign of difference. The purpose of this study was to prove the Mendelian comparison in F2 monohybrid crosses. This research was conducted using 50 pairs of peanuts which were given different colors. A monohybrid cross is a cross that involves one different trait. This experiment was conducted to find out how the genes are paired in crosses. Based on the experimental results to prove Mendel's 1st law, it can be concluded that the F2 cross was carried out 3 times so that finally the cross resulted in a genotypic comparison.